Urgensi Perkembangan Regulasi Mafqud Dalam Mendapatkan Hak Waris - Muhamad Arieva Chandra Aghisna; Sumiyati B; Darmawati Darmawati (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
Determining mafqud status in inheritance is of course still a problem in this research. The judge who made the decision at the Yogyakarta and Bantul Religious Courts through his considerations used the basis of 467 and 468 of the Civil Code which can make a decision after 9 (nine) months. Problems occur when the Heir as an applicant whose object of inheritance is included in the object of compensation for losses on Government Development which has a period of time to fulfill its administration. The absence of norms in determining mafqud status can have legal consequences resulting in the failure to achieve legal objectives. There is very limited material law that is formally contained in the legal regulations for mafqud cases, so judges need to explore, follow and understand the legal values ​​that are developing by paying attention to the provisions of existing legislation and Islamic law contained in fiqh books as a reference and point of reference in examine and decide mafqud cases. Regulations for determining mafqud status are very important considering that dynamic legal developments are a matter of urgency to achieve legal objectives. This research is normative research that is explanatory in nature with a statutory, case approach, and uses secondary data sources obtained from primary, secondary and tertiary legal materials. Collection by literature study and based on the results of the discussion of the main problem, conclusions and suggestions can be drawn.